2018
DOI: 10.1177/1745506518816599
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of risk factors for cervical cancer in the Chinese population

Abstract: Objectives:Human papillomavirus is the necessary cause of cervical cancer, in particular the human papillomavirus-16/18 strains, which have been detected in ~70% of all cervical cancer cases worldwide. This study aims to assess whether other cofactors, which might be specific for the Chinese population, are involved in the development of cervical cancer. These findings may support the future direction of cervical cancer prevention.Study Design:Systematic literature review.Methods:The following databases were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The original systematic review grouped risk factors into 6 main categories and 44 sub-categories. 10 For the present analysis, risk factors were further stratified into more detailed categories to allow meaningful comparison of risks and prevalence. This resulted in 105 different groups of risk factors, which we refer to in the remainder of the article as 105 “risk factors” for simplicity (Supplemental Appendix Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The original systematic review grouped risk factors into 6 main categories and 44 sub-categories. 10 For the present analysis, risk factors were further stratified into more detailed categories to allow meaningful comparison of risks and prevalence. This resulted in 105 different groups of risk factors, which we refer to in the remainder of the article as 105 “risk factors” for simplicity (Supplemental Appendix Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…A random-effects model was chosen because of the heterogeneity across studies observed in the systematic review. 10,12 The random-effects model considered both the variance within studies ( R i ) and the variance between studies ( R i k ) to determine the overall risk R i . The variance within studies relates to the log-study risk, and thus the random-effects model aggregated the transformed log-risks of each study to determine an overall log-risk.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations